2018
DOI: 10.2298/bah1802239k
|View full text |Cite
|
Sign up to set email alerts
|

Toxigenic fungal and mycotoxin contamination of maize samples from different districts in Serbia

Abstract: This study was carried out in order to investigate the natural occurrence of toxigenic fungi and levels of zearalenone (ZEA), deoxynivalenol (DON) and aflatoxin B 1 (AFB 1) in the maize stored immediately after harvesting in 2016 and used for animal feed in Serbia. A total of 22 maize samples were collected from four different districts across the country: City of Belgrade (nine samples), Šumadija (eight samples), Podunavlje (four samples) and Kolubara (one sample). Toxigenic fungi were identified according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In many European countries such as Germany, Hungary, Poland, Romania, AF formation is reported to be low due to weather conditions (Levi c et al, 2013). Although there were studies supporting this finding (Griessler, Rodrigues, Handl, & Hofstetter, 2010;Krnjaja et al, 2018), the literature had many studies with the higher AFs values above the EU regulation limits between 2002 and 2018 years (Kos et al, 2018;Moretti, Logrieco, Visconti, & Bottalico, 2004). In a study conducted in Northern Italy between 2012 and 2013, it was reported that favorable drought conditions caused an increase A. flavus infection, thereby elevating the presence of AFs in maize crops (Perrone, Gallo, & Logrieco, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…In many European countries such as Germany, Hungary, Poland, Romania, AF formation is reported to be low due to weather conditions (Levi c et al, 2013). Although there were studies supporting this finding (Griessler, Rodrigues, Handl, & Hofstetter, 2010;Krnjaja et al, 2018), the literature had many studies with the higher AFs values above the EU regulation limits between 2002 and 2018 years (Kos et al, 2018;Moretti, Logrieco, Visconti, & Bottalico, 2004). In a study conducted in Northern Italy between 2012 and 2013, it was reported that favorable drought conditions caused an increase A. flavus infection, thereby elevating the presence of AFs in maize crops (Perrone, Gallo, & Logrieco, 2014).…”
Section: Discussionmentioning
confidence: 97%